Scoping review of models and frameworks of patient engagement in health services research. Issue 8 (19th August 2022) - Chudyk, Anna Maria; Horrill, Tara; Waldman, Celeste; Demczuk, Lisa; Shimmin, Carolyn; Stoddard, Roger; Hickes, Serena; Schultz, Annette SH
Abstract : Objective: To count and describe the elements that overlap (ie, present in two or more) and diverge between models and frameworks of patient engagement in health services research. Our specific research question was 'what are the elements that underlie models and frameworks of patient engagement in health services research?' Design: Scoping review. Data sources: On 6–7 July 2021, we searched six electronic databases (ie, CINAHL, Cochrane Database of Systematic Reviews, Joanna Briggs Institute Evidence Based Practice Database, MEDLINE, PsycINFO and Scopus) and Google Scholar for published literature, and ProQuest Dissertations & Theses, Conference Proceedings Citation Index, Google, and key agencies' websites for unpublished (ie, grey) literature, with no date restrictions. These searches were supplemented by snowball sampling. Eligibility criteria: We included published and unpublished literature that presented (a) models or frameworks (b) of patient engagement (c) in health services research. We excluded articles unavailable as full text or not written in English. Data extraction and synthesis: Two independent reviewers extracted data from included articles using an a priori developed standardised form. Data were synthesised using both quantitative (ie, counts) and qualitative (ie, mapping) analyses. Results: We identified a total of 8069 articles and ultimately included 14 models and frameworks in the review. These models and frameworks were comprised of 18 overlapping and 57 diverging elements, that were organised into six conceptual categories (ie, principles, foundational components, contexts, actions, levels and outcomes) and spanned intrapersonal, interpersonal, process, environmental, and health systems and outcomes domains. Conclusions: There is little overlap between the elements that comprise existing models and frameworks of patient engagement in health services research. Those seeking to apply these models and frameworks should consider the 'fit' of each element, by conceptual category and domain, within the context of their study.